Visual Database Systems 3 1995
DOI: 10.1007/978-0-387-34905-3_19
|View full text |Cite
|
Sign up to set email alerts
|

Visual construction of highly interactive applications

Abstract: This paper presents Whizz'Ed, an experimental tool for construction of highly interactive or animated applications. Whizz'Ed makes it possible to visually describe by direct manipulation the behaviour of graphical objects and their interrelations. It provides elementary bricks that encapsulate basic interactive behaviours. Whizz'Ed aims at allowing designers to build visual programs in which the control structure is described using data-flows. The flow graph can be structured in order to reuse complex behaviou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
4

Year Published

1999
1999
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 9 publications
(7 reference statements)
2
12
0
4
Order By: Relevance
“…A similar velocity of +27 km s −1 was found from radio recombination lines by Lockman (1989). Esteban & Rosado (1995) concluded that photoionization is the main source of excitation of the inner ring, for which the WR star is mainly responsible. Following the classification by Chu (1991) for WR ring nebulae, they classified the inner nebula as R s type, because it does not present evidence of expansion and its morphology is shell-structured.…”
Section: Background Of CV Ser and Its Close Environssupporting
confidence: 73%
See 3 more Smart Citations
“…A similar velocity of +27 km s −1 was found from radio recombination lines by Lockman (1989). Esteban & Rosado (1995) concluded that photoionization is the main source of excitation of the inner ring, for which the WR star is mainly responsible. Following the classification by Chu (1991) for WR ring nebulae, they classified the inner nebula as R s type, because it does not present evidence of expansion and its morphology is shell-structured.…”
Section: Background Of CV Ser and Its Close Environssupporting
confidence: 73%
“…1.1, Gonzalez & Rosado (1984) and Esteban & Rosado (1995) (using optical lines), and Cappa et al (2002) (using radio continuum data) explained the inner optical bright filament and its radio counterparts as the result of action of the UV field and the strong stellar winds of the star WR 113. An alternative scenario can be proposed taking into account the kinematical properties of Cloud 3, and the location of the WR star and SerOB2-1, -2, -3, -63, and -64.…”
Section: Scenariomentioning
confidence: 96%
See 2 more Smart Citations
“…Cases in which inconsistent distances have been reported in the literature are discussed further in Appendix B. Tuthill et al (2008), (5) Hillenbrand et al (1993), (6) Djurašević et al (2001), (7)Smith (2006), (8) Hur, Sung & Bessell (2012), (9) Davies et al (2012a), (10) Cappa et al (2010), (11) Lundström & Stenholm (1984), (12) Vazquez et al (1995), (13) Kothes & Dougherty (2007), (14) Koumpia & Bonanos (2012), (15) Martín, Cappa & Testori (2007), (20) Esteban & Rosado (1995), (21) Schweickhardt et al (1999). Distance references (1-22 as in Table 1): (23) Arnal et al (1999), (24)Crowther, Smith & Hillier (1995b), (25) Tovmassian, Navarro & Cardona (1996), (26) Howarth & Schmutz (1995), (27) Cappa et al (1999), (28) , (29) Garmany & Stencel (1992), (30) Bohannan & Crowther (1999).…”
Section: Calibration Samplementioning
confidence: 99%